Large low-field-driven electrocaloric effect in organic-inorganic hybrid TMCM-CdCl3 - Yuan Lin; Congcong Chai; Zhijie Liu; Jing Wang; Shifeng Jin; Yurong Yang; Yihong Gao; Munan Hao; Xinyue Li; Yuxuan Hou; Xingyue Ma; Bingjie Wang; et al. (Nature Communications)
Abstract Due to environmental-friendliness and high-efficiency, electrocaloric effect (ECE) is widely regarded as a refrigeration technology for tomorrow. Herein, utilizing organic-inorganic hybridization strategy, we achieve the largest low-field-driven ECE and highest directly-measured electrocaloric strength (ECS) via packing sphere-like organic cation (CH3)3NCH2Cl+ (TMCM+) into inorganic one-dimension (1-D) CdCl3 chain framework. Single-crystal X-ray (SC-XRD) diffraction combined with Raman Spectra reveals that the simultaneous order-disorder transition of organic cations and dramatic structure change of inorganic framework are responsible for the large ECE. Moreover, the measured P-E loops and density function theory (DFT) calculations convey that the distinctive electric-field-induced metastable phase and consequential two-step meta-electric transition could lower the transition energy barrier and account for the low driving field. This work shows that the low-symmetry interaction between inorganic framework and organic cations plays a key role in achieving large ECE under low-field, which provides a method for designing high-performance electrocaloric materials via organic-inorganic hybridization.